Introduction to Terahertz Raman spectroscopy. Issue 8 (14th September 2018) - Bertoldo Menezes, D.; Reyer, A.; Yüksel, A.; Bertoldo Oliveira, B.; Musso, M.
Abstract: This work, intended for advanced undergraduate students, explains the basic concepts and an actual scientific use of Terahertz Raman spectroscopy, displaying some of the benefits of this versatile technique for structural analysis of molecules building up materials since this technique has been increasingly used for molecular characterization in chemistry. A good didactic example of the experimentally applied temperature dependence of molecular vibrations according to the Boltzmann distribution is the ratio of anti-Stokes to Stokes Raman peak intensity used to calculate the temperature of a nylon 6, 6 sample. The comparison of the temperature of nylon 6, 6 calculated from the experimentally determined anti-Stokes to Stokes peak intensity ratio in the Terahertz region with the temperature set with the help of a heating-freezing stage is discussed. The limitations of Terahertz Raman spectroscopy are also part of this fundamental discussion.